2003
DOI: 10.1149/1.1527938
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Granular Cu-Co Alloys

Abstract: Electrodeposition characteristics of Cu-Co films were studied for the formation of heterogeneous alloys for giant magnetoresistance applications. In situ scanning tunneling microscopy, Auger electron spectroscopy ͑AES͒, and high resolution scanning electron microscopy studies showed that rough films with a low concentration of cobalt ͓Cu92.5-Co7.5͔ ͑atom %͒ were deposited mainly due to a higher deposition rate of copper than of cobalt toward the end of the deposition process, and due to the formation of copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In order to obtain a Co-rich deposit at the high-cathodic potential region, the copper sulfate content in the solution was set at significantly low in comparison with the cobalt sulfate. In this system, the film composition is influenced by deposition potential, ion concentration, additives, pH, deposition temperature, and agitation of the solution [7,11,[13][14][15]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a Co-rich deposit at the high-cathodic potential region, the copper sulfate content in the solution was set at significantly low in comparison with the cobalt sulfate. In this system, the film composition is influenced by deposition potential, ion concentration, additives, pH, deposition temperature, and agitation of the solution [7,11,[13][14][15]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrodeposition made the Co-Cu alloy in nonequilibrium supersaturated solid solution state. It is well known that the nucleation-growth process, the morphology, the microstructures, and magnetic properties of Co-Cu electrodeposits depend greatly on solution composition, pH, temperature, and current density or applied potential [11][12][13][14][15][16]. Several baths with different compositions have been used for electrodeposition of CoCu thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In citrate baths, this can be obtained mainly with citrate solution concentration higher than 0.5 mol.L -1 and low polarization values 9 . Cohen-Hyams et al 1 have shown that thin CuCo films presented a negligible concentration of cobalt atoms at the surface, which went through a peak concentration before gradually decreasing close to the substrate, while copper deposition followed the opposite direction. The authors suppose that copper grains are formed on the substrate and, as the deposition process progresses, the substrate changes to the Cu-Co mixture, either as a metastable solid solution and/or as nanoclusters of cobalt inside a matrix of copper.…”
Section: Alloy Electrodepositionmentioning
confidence: 99%
“…Cu-Co alloys, deposited on copper, platinum or silicon substrates, have been presenting great interest due to their possible use in data store systems and sensor technology [1][2][3] . The above mentioned applications are based on the giant magneto resistance properties presented by these alloys, which promotes a great variation of electrical resistance in an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The literature mentioned that pH around 4 was the best for Co electrodeposition onto metal substrate [31,35]. To maintain this pH value, boric acid was frequently used as a buffer agent [28,31,33,35,36].…”
Section: Determination Of Potentials Reduction and Oxidation Of The Cmentioning
confidence: 99%